2021
DOI: 10.3389/fphy.2021.742563
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Based Triboelectric Nanogenerators Using Water Based Solution Process

Abstract: A rapid development in personal electronics has raised challenging requirements for portable and sustainable power sources. For example, in wearable technologies, the concept of wearable body area network brings body motion and vital signs monitoring together in synergy. For this, a key aspect is sustainable portable energy, available anywhere, at any time, as generated by triboelectric nanogenerators (TENG). This technology usually demands high-cost processes and materials and still suffer from low power outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…To implement solution-based methods in fabrication of TENGs, Domingos et al [56] introduced shear-exfoliated graphene electrodes to enhance the flexibility of the device. SEG flakes were obtained from graphite by solution-processed method using sodium cholate as J o u r n a l P r e -p r o o f surfactant.…”
Section: Shear Exfoliated Graphene Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…To implement solution-based methods in fabrication of TENGs, Domingos et al [56] introduced shear-exfoliated graphene electrodes to enhance the flexibility of the device. SEG flakes were obtained from graphite by solution-processed method using sodium cholate as J o u r n a l P r e -p r o o f surfactant.…”
Section: Shear Exfoliated Graphene Electrodesmentioning
confidence: 99%
“…SEG flakes were obtained from graphite by solution-processed method using sodium cholate as J o u r n a l P r e -p r o o f surfactant. Two TENG devices were fabricated using graphene and aluminium as back electrodes in order to compare the performance of metal and carbon electrodes [56]. A maximum power density of 13.14 μW/cm 2 is achieved which is 40 times higher than that from aluminium electrodes based TENG.…”
Section: Shear Exfoliated Graphene Electrodesmentioning
confidence: 99%
“…[116][117][118] Numerous studies have indicated significant improvements in TENG performance with the use of various 2D materials. [33,119,120] The use of 2D materials in the fabrication of textile-based wearable TENGs has resulted in considerable improvements in mechanical and electrical performance. [121][122][123][124][125][126] These findings demonstrate that 2D materials are absolutely fascinating candidates for mechanical energy harvesting applications in wearable textiles.…”
Section: Triboelectric Nanogeneratormentioning
confidence: 99%
“…Other alternatives have also been tested using carbon-based materials, such as carbon nanotubes or graphene, which offer excellent performance under harsh mechanical deformation or even conductive textiles (Haque et al, 2018;Khan et al, 2017;Tian et al, 2018;Domingos et al, 2021). Mainly targeting applications in fabric, they also offer compatible processing deposition with textiles.…”
Section: Conductive Materialsmentioning
confidence: 99%